2018
DOI: 10.1007/s00216-018-1134-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the aroma profile of novel Brazilian wines by solid-phase microextraction using polymeric ionic liquid sorbent coatings

Abstract: In this study, a series of polymeric ionic liquid (PIL) sorbent coatings is evaluated for the extraction of polar volatile organic compounds (VOCs) from Brazilian wines using headspace solid-phase microextraction (HS-SPME), including samples from 'Isabella' and 'BRS Magna' cultivars-the latter was recently introduced by the Brazilian Agricultural Research Corporation - National Grape & Wine Research Center. The structurally tuned SPME coatings were compared to the commercial SPME phases, namely poly(acrylate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 63 publications
0
11
0
2
Order By: Relevance
“…Some studies have highlighted characteristics in juices made from 'BRS Magna' grapes, including basic components of quality, phenolic profile and contents, antioxidant activity and volatile organic compounds (Crucello et al, 2018;Lima et al, 2014;Mariani;Nava, 2018;Ristchel et al, 2014). Aspects of phenology, adaptation to different regions and yield performance have also been evaluated (Ritschel et al, 2014;Leão at al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have highlighted characteristics in juices made from 'BRS Magna' grapes, including basic components of quality, phenolic profile and contents, antioxidant activity and volatile organic compounds (Crucello et al, 2018;Lima et al, 2014;Mariani;Nava, 2018;Ristchel et al, 2014). Aspects of phenology, adaptation to different regions and yield performance have also been evaluated (Ritschel et al, 2014;Leão at al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for unique selectivity, ionic‐liquid coatings have been recently developed for sampling methods [76,77], in addition to their use as stationary phase for GC columns [78,79]. Few recent pieces of research reported on the use of poly ionic‐liquid (PIL)‐based sorbent coatings for HS‐SPME in GC×GC [80,81]. Crucello et al.…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…Crucello et al. investigated several non‐ionic and PIL‐based sorbent coatings for HS‐SPME, analyzing VOCs in Brazilian wine [80]. About 350 peaks were detected in four wine samples.…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…This item is focused on the discussion of the advances achieved by GCxGC in studies that have not used the olfactometric resource. According to Table 4, olfactometry is not usually used in GCxGC investigations; and inferences about the possible contribution of the volatile compounds to aroma are performed from the description of odor reported in the literature [7,9,19,116–122].…”
Section: Comprehensive Two‐dimensional Gas Chromatography In Wine Anamentioning
confidence: 99%